Simulation and Optimization of A Crude Oil Distillation Unit - Kamışlı, Fethi; Ahmed, Ari Abdulqader (Fırat University, 2019)
In the present study simulation and optimization of a crude oil distillation unit of a refinery by Aspen HYSYS simulation program has been carried out with the aim of increasing the efficiency of the unit. The effects of the temperature of the kerosene removal plate, the cap temperature of the distilling tower, the stripping steam flow and the top pressure of the tower on the distillation products were determined for the aim of increasing yields of some valuable products. The yield of kerosene increased to be 5.98 % by varying the temperature of the kerosene removal plate from 202 ?C to 206 ?C. It was observed that the decrease in the cap temperature and the increase in both the stripping steam flow and the tower feeding temperature increase flow rates of both the kerosene and the naphtha cuts. It was noted that the adjustment such as the reduction of the tower pressure from 1.7 kg/cm2 to 1.5 kg/cm2 generates the greatest impact on the yields of the products with the highest commercial value without generating additional costs. The optimum operation conditions determined by the simulation increased the efficiency of the plant in terms of higher yields of both kerosene and naphtha.
Keywords: Engineering; Mühendislik